Empire and slavery in American literature, 1820-1865 - Sundquist, Eric J. (University Press of Mississippi, 2006)
The flourishing of pre-Civil War literature known as the American Renaissance occurred in a volatile context of national expansion and sectional strife. Canonical writers such as Herman Melville, Walt Whitman, Emily Dickinson, and Henry David Thoreau, as well as those more recently acclaimed, such as Frederick Douglass and Harriet Beecher Stowe, emerged amidst literature devoted to questions of nationalism, exploration, empire, the frontier, and slavery. This outpouring included some of the most important early works in African American, American Indian, and Chicana/Chicano literature. Empire.